Preclinical advances and the immunophysiology of a new therapeutic Chagas disease vaccine. (2nd September 2022) - Jones, Kathryn M.; Poveda, Cristina; Versteeg, Leroy; Bottazzi, Maria Elena; Hotez, Peter J.
ABSTRACT: Introduction: Chronic infection with the protozoal parasite Trypanosoma cruzi leads to a progressive cardiac disease, known as chronic Chagasic cardiomyopathy (CCC). A new therapeutic Chagas disease vaccine is in development to augment the existing antiparasitic chemotherapy drugs. Areas Covered: We report on our current understanding of the underlying immunologic and physiologic mechanisms that lead to CCC, including parasite immune escape mechanisms that allow persistence and the subsequent inflammatory and fibrotic processes that lead to clinical disease. We report on vaccine design and the observed immunotherapeutic effects including induction of a balanced TH 1/TH 2/TH 17 immune response that leads to reduced parasite burdens and tissue pathology. Furthermore, we report vaccine-linked chemotherapy, a dose-sparing strategy to further reduce parasite burdens and tissue pathology. Expert Opinion: Our vaccine-linked chemotherapeutic approach is a multimodal treatment strategy, addressing both the parasite persistence and the underlying deleterious host inflammatory and fibrotic responses that lead to cardiac dysfunction. In targeting treatment towards patients with chronic indeterminate or early determinate Chagas disease, this vaccine-linked chemotherapeutic approach will be highly economical and will reduce the global disease burden and deaths due to CCC.